A Modified Preparation of Cellulosic-Absorbent Resin for Cu2+ Removal under Microwave Irradiation - Jing Shu; Dabiao Zhao; Lili Li (Advances in Materials Science and Engineering)
The absorbent resin for Cu2+ removal was prepared under microwave irradiation through grafting acrylamide (AM) and acrylic acid (AA) to cellulose. The initiator is a kind of redox system composed of potassium persulfate/sodium thiosulfate. The crosslinking agent is N,N′-methylene bisacrylamide. The optimal reaction conditions are as follows: the ratio of AA to cellulose is 10 : 1, initiator to AA is 0.65 wt%, crosslinking agent to AA is 1.0 wt%, neutralization degree of AA is 75%, microwave power level is 320 W, and time is 300 s. The maximum absorption capability of the resin is 65 mg·g−1. Different from previous studies, the reaction was carried out without the protection of nitrogen and troublesome posttreatment. The product was obtained directly by one-step synthesis without purification and drying of the crude product. The pollution and cost caused by organic solvent are avoided, and the whole preparation period is shortened deeply. Moreover, the time of absorption equilibrium is shorter. In a word, the preparation in this paper has the obvious advantages, such as simple process, short time, no pollution, low-energy, and low-cost.